Long-Term Clinical Outcomes of Small-Incision Femtosecond Laser-Assisted Intracorneal Concave Lenticule Implantation in Patients with Keratoconus. (16th March 2022) - Wei, Qi; Ding, Hui; Nie, Ke; Jin, He; Zhong, Tan; Yu, Hanyang; Yang, Zhenduo; Hu, Shisi; He, Linyi; Zhong, Xingwu
Abstract : Purpose . The purpose of this study was to evaluate the long-term prognosis of small-incision femtosecond laser-assisted intracorneal concave lenticule implantation (SFII) in correction of human keratoconus. Methods . This was a prospective study for 11 patients who received SFII after being diagnosed as progressive keratoconus based on the Amsler–Krumeich classification system. Clinical assessment was performed for all the patients prior to and postsurgically at different time points for 5 years. These included uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), biomechanically corrected intraocular pressure (bIOP), corneal topography, anterior segment optical coherence tomography (AS-OCT), confocal microscopy, and biomechanical assessment with Corvis ST. Results . Comparison of preoperative and 60-month postoperative UDVA and CDVA (P 60 months = 0.081 and 0.001, respectively), all eyes showed an improvement in CDVA. Corneal topography showed no significant changes in corneal anterior K1, K2, posterior K1, K2, posterior elevation, or corneal densitometry compared with preoperative levels (P > 0.05 ). Corvis ST showed that central corneal thickness (CCT) and stiffness at applanation 1 (SP-A1) were significantly greater 1 week postsurgically when compared to the baseline (P < 0.05 ) and remained stable thereafter. The lenticule under the AS-OCT remained transparent throughout the entire postsurgical period. Under confocal microscopy, corneal edema and an increase in cell activation and reflectivity were observed at the lenticule-stromal interface within 1 week postoperatively. These reactions gradually subsided with time within 6 months. Conclusion . SFII is an effective procedure to prevent the progression of keratoconus due to its minimal invasiveness and capability of maintaining a steady biometry of the cornea.